Clinical features of pituitary carcinoma: analysis based on a case report and literature review - Yang, Yongxiang; Liang, Wanlin; Fan, Kexia; Yang, Tao; Cheng, Jingmin (Frontiers in Endocrinology, 2024)
Pituitary carcinoma (PC) is an extremely rare tumor of the adenohypophysis, which manifests as craniospinal dissemination and/or systemic metastasis. The diagnosis of PC is particularly difficult, as the clinical diagnosis only can be made after the metastasis is found. Owing to the complex diagnostic process and less effective treatments, the clinical prognosis of PC is usually very poor. Hence, it is of great significance to illustrate the diagnosis and treatment course of PC. In this case report, we described a 48-year-old male patient was diagnosed as pituitary adenoma (PA) initially, then was diagnosed as PC eventually after the spinal cord metastasis was found, and the treatment course was illustrated as well. Furthermore, we summarized all the published case reports until now and provided a comprehensive review for the diagnosis, treatment, prediction and clinical outcome for PC. We found most PC patients were ACTH/PRL-secreting tumors, Ki-67≥10% and P53 positive might have the potential to predict the transformation from PA to PC, surgery excision combined with temozolomide (TMZ) and radiotherapy is helpful to prolong the survival of PC patients.